Pengaruh Komunikasi Organisasi, Organizational Culture, Dan Leadership Style Terhadap Kinerja Pengurus (Studi Kasus pada Formas Malang Raya 2021/2022) - Arya Wega Nanda; Pardiman Pardiman; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of organizational communication, organizational culture, and leadership style on the performance of Formas Malang Raya 2021/2022 management. The location of this research was carried out on active members of the 2021/2022 Malang Raya Formation. This research is a quantitative research. This study used the case study method where data was obtained by distributing questionnaires to members of the Malang Raya 2021/2022 Formas management who were selected using a simple random sampling technique. Determining the number of samples using the slovin formula with the results of 90 respondents. Data were analyzed using multiple linear regression tests and determination tests. Based on the results of data analysis, the results of the F test show that simultaneously affective commitment, continuing commitment, and normative commitment have a significant effect on the performance of Formas Malang Raya 2021/2022 management. Furthermore, the results of the t test show that organizational communication, organizational culture, and leadership style have a positive and significant effect on the performance of Formas Malang Raya 2021/2022 management. The results of the determination test show a proportion of 78.2%, where the performance of the board can be influenced by organizational communication, organizational culture, and leadership style. It is suggested to the next researcher that it is expected to be able to examine the performance of the management using another methodology due to the possibility of bias towards the respondents' answers in the questionnaire. Keywords : Management Performance, Organizational Communication, Organizational Culture, Leadership Style.